2018
DOI: 10.4193/rhin17.226
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of efficacy of fluticasone propionate versus clarithromycin for postoperative treatment of different phenotypic chronic rhinosinusitis: a randomized controlled trial

Abstract: Background: Chronic rhinosinusitis (CRS) can be divided to CRS without nasal polyps (CRSsNP) and eosinophilic and non-eosinophilic CRS with nasal polyps (CRSwNP). There is little evidence on the efficacy of glucocorticoids and macrolides in different phenotypic patients. The aim of this study was to compare the benefit of glucocorticoids and macrolides following endoscopic sinus surgery (ESS) in different phenotypic CRS. Methods:This study was a prospective single-blind comparative effectiveness trial. A total… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
62
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(62 citation statements)
references
References 39 publications
0
62
0
Order By: Relevance
“…In addition to improvements in the above outcomes, RWE studies reported that non-biologics improved SNOT-22 scores, Lund-Kennedy CT and endoscopic scores, total symptom scores by VAS, and nasal polyp scores (Supplementary Tables 5, 7 , 9, 11, 13, and 14). Four RCTs [77][78][79][80] and 4 RWE studies [81][82][83][84] reported on non-biologics (corticosteroids and ESS) for patients with eCRSwNP. All eight studies demonstrated improvement in clinical outcomes.…”
Section: Results For Non-biologicsmentioning
confidence: 99%
“…In addition to improvements in the above outcomes, RWE studies reported that non-biologics improved SNOT-22 scores, Lund-Kennedy CT and endoscopic scores, total symptom scores by VAS, and nasal polyp scores (Supplementary Tables 5, 7 , 9, 11, 13, and 14). Four RCTs [77][78][79][80] and 4 RWE studies [81][82][83][84] reported on non-biologics (corticosteroids and ESS) for patients with eCRSwNP. All eight studies demonstrated improvement in clinical outcomes.…”
Section: Results For Non-biologicsmentioning
confidence: 99%
“…The authors concluded that CRSsNP and longer duration of treatment (24 weeks) were predictors of success (7) . The other factors were not helpful, particularly in the postoperative period, where there does not seem to be an additive effect of macrolides over nasal corticosteroids alone (7,8) . Recently it was proposed to systematically use eosinophils (as a marker of Th2 disease) on top of phenotyping based on the presence of nasal polyps, to differentiate treatments in CRS (9) .…”
Section: Long-term Antibiotics For Chronic Rhinosinusitis: Changing Vmentioning
confidence: 97%
“…We found that 82.1% (110/134) of patients with loss of sense of smell and 95.5% (231/242) of patients with loss of taste recovered in one month after discharge. The symptomatic duration days showed no difference between the patients with loss of smell and taste (8 [6-13.25] vs 7 [5][6][7][8][9][10][11][12][13][14] days, P = 0.52) (Fig 1, C). Most of them recovered in 14 days after onset of symptom (Fig 1, D).…”
Section: The Recovery Of Olfactory and Taste Functionmentioning
confidence: 96%
“…More COVID-19 cases with severe illness were found in the severe loss of taste group than in the moderate loss of taste group (26.9% vs 12.7%, P = 0.03). The symptom duration of loss of taste was signi cantly longer in moderate and severe taste dysfunction group as compared to the mild taste dysfunction group (8 days [6-13.25], 10 days [5][6][7][8][9][10][11][12][13][14][15] vs 5 days [3.5-8], P < 0.01) (Fig 2). In addition, serum levels of interleukin-6 (IL-6) and lactate dehydrogenase (LDH) were signi cantly increased in patients with severe compared to mild and moderate loss of taste group (Table 2).…”
Section: Clinical Characteristics Of Covid-19 Patients With Differentmentioning
confidence: 99%
See 1 more Smart Citation